The Interconnectedness of Mathematics and Music Teaching Contents in the Lower Grades of Elementary School - Jelena M. Savić (University of Belgrade, Teacher Education Faculty, 2018)
The content of the paper is focused on determining the efficiency of an experimental program based on linking mathematics and music content in order to manage the material in both subjects better in the lower grades of elementary school. Contemporary teaching aims at linking the contents of different subjects to make pupils' knowledge more lasting and teaching more effective. In this paper, we will point out the contents of mathematics in which it is possible to implement music teaching content and vice versa in order to improve the cognitive development of children of the lower school age. The aim of the research is the experimental study of the effects of a teaching approach in which the teaching contents of mathematics and music are linked. An experimental method was used, based on which we obtained the basic result that the knowledge of fractions is helpful in learning the tone duration (and vice versa). Given that we also observed a poor knowledge of the basic elements of musical literacy among students, we emphasize the possibility of improving students' learning motivation by applying the mathematics contents that are essentially related to specific music contents.